Rancang Bangun Website Galacticos Fc Bireuen - Sriwinar; Riyadhul Fajri; Andre Maireza (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
Football is one of the most popular sports in the world. This sport is played by two opposing groups, each of which struggles to get the ball into the opposing group's goal. Each group consists of eleven players and therefore the group is also called a team. Aceh province has several football teams that compete in League 2 and League 3 under the auspices of the All-Indonesian Football Association (PSSI). Every football team has a stadium as a home base that is used for matches. Along with the large number of teams in Aceh Province, there are problems namely, how to analyze information, monitor team progress and provide information related to spatial and non-spatial data. In this study, the authors create a web-based system that displays biodata of players, administrators, and officials. This system is built using the codeigniter framework with Sbadmin2 and Mysql templates as databases.